2012
DOI: 10.1021/am201564f
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Impact Toughness of Poly(l-lactide)/Poly(ε-caprolactone) (PLLA/PCL) Blends by Controlling Crystallization of PLLA Matrix

Abstract: Melt blending poly(L-lactide) (PLLA) with various biodegradable polymers has been thought to be the most economic and effective route to toughen PLLA without compromising its biodegradability. Unfortunately, only very limited improvement in notched impact toughness can be achieved, although most of these blends show significant enhancement in tensile toughness. In this work, biodegradable poly(ε-caprolactone) (PCL) was used as an impact modifier to toughen PLLA and a nucleating agent was utilized to tailor the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
180
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(193 citation statements)
references
References 59 publications
5
180
2
2
Order By: Relevance
“…This observation is well consistent with the deteriorated impact toughness of the blends with high-concentration TiO 2 as mentioned above. In addition, our previous work has shown that the crystallinity of PLLA matrix may influence the impact toughness of PLLA/elastomer blend [53]. However, it can be disregarded completely in this work.…”
Section: Toughening Mechanismmentioning
confidence: 95%
“…This observation is well consistent with the deteriorated impact toughness of the blends with high-concentration TiO 2 as mentioned above. In addition, our previous work has shown that the crystallinity of PLLA matrix may influence the impact toughness of PLLA/elastomer blend [53]. However, it can be disregarded completely in this work.…”
Section: Toughening Mechanismmentioning
confidence: 95%
“…7e, which is much larger than the optimum size (~0.75 μm) for highly toughened amorphous or low crystalline PLLA matrix [57]. The enhancement in molecular entanglement of the matrix by incorporation of PDLA is helpful for improving impact strength of PLLA [48], while higher crystallinity of the matrix is harmful, because it would make the matrix shear yielding more difficult [58]. The combination of the variations of phase morphology, molecular entanglement and matrix crystallinity accounts for the variation tendency of the blends versus PDLA content.…”
Section: Notched Izod Impact Strengthmentioning
confidence: 97%
“…This is the most often used definition of toughness, although on occasions compression testing has been performed for an analogous purpose. The term "toughness" is also applied to the key result of impact testing, namely the energy necessary to cause fracture at high rates of force application [4,5]. Thus there exists fracture toughness, notch toughness, determined in impact testing for a predetermined geometry of the notch and testing method (e.g.…”
Section: Introduction and Scopementioning
confidence: 99%